KEBUNTINGAN SAPI BALI YANG DIINSEMINASI BUATAN SETELAH MENUNJUKKAN BIRAHI ALAMI - Hasrin Hasrin; Abd. Latief Toleng Toleng; Hasbi Hasbi (Universitas Islam Balitar, 2022)
Lower conception rate of cows in the tropics might be affected by low quality of semen collected from bulls consumed low quality food. This study was conducted to evaluate the conception rate of Bali cows natural estrus inseminated with semen of the bulls supplemented with Moringa oleifera leaf (MOL) powder blocks. There were 51 Bali cows 3-4 years of age, non pregnant and having corpus luteum, used in this study. They were divided into 2 groups, group 0 (G0, n=23) were inseminated with commercially available semen. Group 1 (G1, n=28) were inseminated with semen of bulls supplemented with MOL powder blocks. All cows were artificially inseminated after natural estrus. Pregnancy diagnosis were perfomed by rectal palpation 60 days after the insemination. The mean diffents between the two treatments were analyzed by chi-squared analysis. Although statistical analysis showed that there was not different between the two treatments (P>0.05), but economically, the treatment of G1 could increase 10 % of conception rate. It can be concluded that the supplementation of MOL powder block could increase the conception rate of Bali cows natural estrus.